â€œI Have to Teach The â€˜Englishâ€™ Englishâ€: Native-speakerism Ideology among the English Teachers - Harsanti, HG Retno; Manara, Christine (Indonesian Journal of Applied Linguistics, 2021)
Native-speakerism is a crucial issue to discuss in ELT, especially related to the different ideological views on World Englishes and â€˜standardâ€™ English. Differences in ideology about English and its variations have an impact on the English teaching implementation. Many studies have examined discrimination practices driven by native-speakerism ideology in educational contexts such as in the preference of English teacher recruitment which prefers teachers who are considered as native speakers. Although studies have discussed native-speakerism ideology, not many studies have discussed native-speakerism ideology from the perspective of English teachers in Indonesia. This study, therefore, aims to find out how widespread this ideology is among English teachers of a private school in metropolitan Jakarta. It seeks to explore the dimensions of native-speakerism in the various aspects of the English teaching profession. This study is interview-based research with seven participants. Data collection was done by conducting individual interviews for 30-40 minutes which then were analyzed descriptively to identify the recurring themes. The results showed that there were traces of native speakerism ideology among the English teachers in Permata schools that views English from a purist perspective towards the language and its culture. This purist perspective is reflected from how they defined native-speakers of English and depicted the ownership of English, language learning and teaching beliefs, and their teaching practices.